Sex Differences in Brain Injury and Repair in Newborn Infants: Clinical Evidence and Biological Mechanisms - Rosenkrantz, Ted S.; Hussain, Zeenat; Fitch, Roslyn Holly (Frontiers in Pediatrics, 2019)
Differences in the development of the male and female brain are an evolving area of investigation. We are beginning to understand the underpinnings of male and female advantages due to differences in brain development as well as the consequences following hypoxic-ischemic brain injury in the newborn. The two main factors that appear to affect outcomes are gestation age at the time of injury and sex of the subject. This review starts with a summary of differences in the anatomy and physiology of the developing male and female brain. This is followed by a review of the major factors responsible for the observed differences in the face of normal development and hypoxic injury. The last section reviews the response of male and female subjects to various neuroprotective strategies that are currently being used and where there is a need for additional information for more precise therapy based on the sex of the infant.